Student engagement in two Singaporean secondary schools - Tan, Yuen Teng (2016)
Student engagement is important to prevent school dropout and enhance school experiences. Engagement of secondary 2 and 3 students in Singapore was studied with Student Engagement Instrument (SEI) and its relation to burnout. The SEI measured students’ cognitive and affective engagement while burnout was examined using School Burnout Inventory (SBI). An electronic survey was administered to 335 students from two secondary schools. The engagement and burnout across grades, streams, gender, academic achievements and family background were studied. Evidence showed lower engagement for secondary three than two students, while ethnicity had a major impact on engagement level, with minority ethnic groups (Malays, Indians and Others) being more engaged than Chinese, the largest ethnic group. Lastly, engagement and burnout had a negative but weak correlation.